A network system for the prevention and treatment of mushroom poisoning in Chuxiong Autonomous Prefecture, Yunnan Province, China: implementation and assessment - Qunmei Yao; Zhijun Wu; Jiaju Zhong; Chengmin Yu; Haijiao Li; Qiuling Hu; Jianrong He; Jianping Du; Chengye Sun (BMC, 2023)
Abstract Background Mushroom poisoning is a major public health issue in China. The integration of medical resources from different institutes of different levels is crucial in reducing the harm of mushroom poisoning. However, few studies have provided comprehensive implementation procedures and postimplementation effectiveness evaluations. To reduce the harm caused by mushroom poisoning, a network system for the prevention and treatment of mushroom poisoning (NSPTMP) was established in Chuxiong, Yunnan Province, a high-risk area for mushroom poisoning. Methods The NSPTMP consists of three types of institutions, namely, centers for disease prevention, hospitals, and health administration departments, with each kind of institution comprising prefecture, county/city, town, and village levels. After three years of implementation, the network was evaluated by comparing the indices before and after network implementation using data from the "Foodborne Disease Outbreak Surveillance System" and 17 hospitals in Chuxiong. The indices included the fatalities caused by mushroom poisoning, the composition ratios of different types of mushrooms for both outpatients and inpatients and the hospitalization rates. Results Compared to the average fatality rate of mushroom poisoning from 2015 to 2017, the average fatality rate from 2018 to 2020 significantly decreased from 0.57 to 0.06% (P < 0.001). Regarding the poisonous genus containing lethal mushrooms, the outpatient and inpatient composition ratios significantly decreased for Amanita (9.36-2.91% and 57.23-17.68%, respectively) and Russula (15.27-8.41%) (P < 0.05). Regarding poisonous mushrooms that caused mild symptoms, the outpatient and inpatient composition ratios significantly increased for Scleroderma (5.13-13.90% and 2.89-18.90%, respectively) and Boletaceae (19.08-31.71%) (P < 0.05), and the hospitalization rates significantly increased for Scleroderma (6.33-18.02%) and Boletaceae (5.65-12.71%) (P < 0.05). Conclusions These findings suggest that the NSPTMP effectively reduced the harm caused by mushroom poisoning. In addition to the integration of medical resources, the development of poisonous mushroom identification, hierarchical treatment systems in hospitals, public education, and professional training also played important roles in improving the system's effectiveness. The establishment and evaluation of the NSPTMP in Chuxiong Prefecture can provide valuable insights and serve as a model for other regions facing similar challenges in managing mushroom poisoning.